Phenotypic performance of rice landraces under salinity stress in reproductive stage (Progressive Agriculture, 2017)
An experiment was conducted using a randomized complete block design to explore the performance of rice landraces under salinity stress condition at Plant Breeding Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. The experiment was consisted of five replication and three different salt treatments viz., EC-6 dSm-1, EC-8 dSm-1, EC-12 dSm-1 with one control condition. Analysis of variance for yield and yield contributing traits showed significant (p